2010
DOI: 10.3892/or_00000873
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of thymidine phosphorylase-positive macrophages is closely associated with tumor angiogenesis and survival in intestinal type gastric cancer

Abstract: Abstract. Thymidine phosphorylase (TP), an enzyme catalyzing the reversible phospholysis of thymidine, deoxyuridine and their analogs at their respective bases and 2-deoxyribose-1-phosphate, thus promoting angiogenesis, is often expressed in macrophages present in tumor stroma. In this study, we investigated whether infiltration of TP-positive macrophages as well as tumor-associated macrophages affected tumor angiogenesis. TP was expressed in human macrophage-like cells, but not in gastric cancer cells in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 25 publications
1
49
1
1
Order By: Relevance
“…Stage of Human Gastric Cancers-TAMs are associated with poor prognosis in gastric cancer (36). To provide some information regarding EGFR in macrophages in human cancers, we sought to study whether there is a correlation between the level of EGFR expression in macrophages in cancer tissues and tumor development.…”
Section: Expression Of Egfr In Macrophages Is Decreased In the Latementioning
confidence: 99%
“…Stage of Human Gastric Cancers-TAMs are associated with poor prognosis in gastric cancer (36). To provide some information regarding EGFR in macrophages in human cancers, we sought to study whether there is a correlation between the level of EGFR expression in macrophages in cancer tissues and tumor development.…”
Section: Expression Of Egfr In Macrophages Is Decreased In the Latementioning
confidence: 99%
“…TAMs, in particular, have been found to be associated with tumor growth and metastasis (5)(6)(7). A large number of studies concerning numerous tumor types, including colorectal cancer (5), supraglottic laryngeal carcinoma (6), Ewing's sarcoma (7), intestinal type gastric cancer (29), pancreatic cancer (30), non-gynecologic leiomyosarcoma (31) and thyroid cancer (32), have shown that the presence of TAMs in the tumor microenvironment is associated with a worse prognosis. Therefore, TAMs play an important role in tumor progression.…”
mentioning
confidence: 99%
“…Однако большинство исследова-ний свидетельствует о том, что высокая плотность макрофагов связана с факторами неблагоприятного прогноза и ухудшением отдаленных результатов лечения больных раком желудка [33,80,81].…”
Section: Foxp3unclassified